The previous evaluation process in business mergers and acquisitions in Peru - Verástegui Corrales, Cleofé Maritza (2018)
Objective: To optimize the process of prior evaluation in mergers and acquisitions in Peru. Method: It is a descriptive and correlational investigation. The comparative law was used as analysis methodology for the law projects under study. Results: In the analysis of the economic impact, the sample consisted of 1 750 companies according to annual sales value and economic sectors such as lawyer services and agroindustries. The results indicated that the Proposals of Application of Thresholds on Projects of Law lack foundation and it has been verified that its uniformly application might be ineffective to all the economic sectors. Conclusions: The improvement of the process of prior evaluation in mergers and acquisitions will create an environment of trust in the CEOs of Peruvian companies, strengthen the capital and securities markets and contribute to the sustained growth of the country due to the whole favorable environment outlook